An assessment of heritage property values using multiple regression analysis : Georgetown, Penang Island Malaysia / Nur Shahirah Ja’afar and Junainah Mohamad - Ja’afar, Nur Shahirah; Mohamad, Junainah (Universiti Teknologi MARA, Perak, 2020)
The aim of this paper was to estimate the value of heritage property using multiple regression analysis. The original dataset consists of 311 Pre-war Shophouses transacted from 2004 to 2018 in Northern-Eastern of Penang Island, Malaysia. After filtration process, only 248 units of Pre-war Shophouses heritage property were available and valid to be used. Three functional forms such as linear, semi-log and log-log have been constructed and their statistical performances have been compared. The results indicate that log-log functional form performed better than the other functional forms in predicting the price of heritage property.